The effect of Substance P/Heparin conjugated PLCL polymer coating of bioinert ePTFE vascular grafts on the recruitment of both ECs and SMCs for accelerated regeneration - Kim, Donghak; Chung, Justin J.; Jung, Youngmee; Kim, Soo Hyun (NATURE PUBLISHING GROUP, 2019)
Artificial vascular grafts consisting of ePTFE have been mainly used in clinics for the treatment of cardiovascular disease. However, artificial grafts can become clogged after a long time due to thrombosis, as graft maturation by endothelialization is limited. The strategy introduced in this study is to induce graft remodeling through interaction between the bioinert graft and the body. The Substance P (SP) and heparin were covalently conjugated with PLCL, an elastic biocompatible copolymer and the Substance P-conjugated PLCL (SP-PLCL) and/or heparin-conjugated PLCL (Hep-PLCL) were vacuum-coated onto ePTFE vascular grafts. To assess the effectiveness of the coating, coated samples were evaluated by implanting them subcutaneously into SD-Rats. Coatings allow grafts to be remodeled by creating a microenvironment where cells can grow by infiltrating into the grafts while also greatly enhancing angiogenesis. In particular, a double coating of Hep-PLCL and SP-PLCL (Hep/SP-PLCL) at four weeks showed markedly improved vascular remodeling through the recruitment of mesenchymal stem cells (MSCs), vascular cells (ECs, SMCs) and M2 macrophages. Based on these results, it is expected that when the Hep/SP-PLCL-coated ePTFE vascular grafts are implanted in situ, long-term patency will be assured due to the appropriate formation of an endothelial layer and smooth muscle cells in the grafts like native vessels.
Keywords: MESENCHYMAL STEM-CELLS; SMOOTH-MUSCLE-CELL; TISSUE-REPAIR; COVALENT IMMOBILIZATION; EXTRACELLULAR-MATRIX; HEPARIN; ENDOTHELIALIZATION; SCAFFOLDS; NEOVASCULARIZATION; MACROPHAGES